Strategi Strategi Kepala Sekolah Dalam Pemanfaatan Media Sosial Terhadap Peningkatan Komunikasi Dan Kolaborasi Antara Guru, Orang Tua, Dan Siswa Di SDN 2 Suangi: social media, principal, communication, collaboration, parental involvement - Ahadiah; pashur, Pashurrahman; Qusyairi, Lalu A Hery; Anwar, Khairil; Zainudin, Zainudin; Panjaitan, Ajhari (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to describe the principal's strategy in utilizing social media to enhance communication and collaboration among teachers, parents, and students at SDN 2 Suangi. A descriptive qualitative approach was applied, with data collected through observation, interviews, and documentation. The findings revealed that the strategy began with a needs and readiness survey among school stakeholders, followed by selecting WhatsApp as the main communication platform due to its accessibility, familiarity, and cost-effectiveness. Social media was proven effective in accelerating two-way communication and increasing parental involvement. Despite challenges such as low digital literacy and uneven participation, the strategy successfully fostered a collaborative atmosphere and strengthened student learning support at home and school. These results highlight the importance of wisely integrating social media into school communication management, considering accessibility, digital education, and proper supervision. In addition, a well-planned integration of social media can serve as a reference for school principals in optimizing technology-based communication management within elementary education settings.